2012
DOI: 10.2214/ajr.11.8182
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT of Cancer Patients: Part 1, Pancreatic Neoplasms

Abstract: Multimodality imaging is critical in the diagnosis and management of pancreatic cancer. PET/CT is increasingly viewed as a useful, accurate, and cost-effective modality in diagnosing and managing pancreatic cancer, but further studies are warranted. Early data suggest that contrast-enhanced PET/CT performed with modern PET/CT scanners yields high-resolution anatomic information for surgical and radiotherapeutic planning and functional information for whole-body staging in the care of patients with this disease. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 75 publications
0
46
0
2
Order By: Relevance
“…PET/CT is a useful imaging test in staging, therapy response assessment, and follow-up of patients with many human solid tumors (7)(8)(9)(10)(11)(12), including head and neck cancers (13)(14)(15)(16)(17). The objective of this article is to review the evolving role of PET/ CT in staging, therapy response assessment, and follow-up of patients with HPV-positive OPSCC.…”
mentioning
confidence: 99%
“…PET/CT is a useful imaging test in staging, therapy response assessment, and follow-up of patients with many human solid tumors (7)(8)(9)(10)(11)(12), including head and neck cancers (13)(14)(15)(16)(17). The objective of this article is to review the evolving role of PET/ CT in staging, therapy response assessment, and follow-up of patients with HPV-positive OPSCC.…”
mentioning
confidence: 99%
“…There is always a need for better imaging modalities for diagnosis, staging, treatment designing, evaluating response and envisaging result when we are dealing with diseases of such burden. Among such advanced imaging modalities, FDG PET/CT radiotracer imaging is one of the valued modality (27). FDG-PET/CT gives convincing results in detecting tumor size and shape, occult primary tumors, locoregional nodal spread, and distant metastases (28)(29)(30).…”
Section: Nuclear Imaging In Head and Neck Cancermentioning
confidence: 99%
“…Overexpression of GLUT-1 and hexokinase-Ⅱ has been reported in PC [23] . In patients with PC, several studies have demonstrated that 18 F-FDG PET/CT was an important key factor for in staging, detecting postoperative recurrence, and evaluating the response to treatment [24][25][26][27][28] . The recent typical researches and interest findings were listed in the follow.…”
Section: F-fluorodeoxyglucosementioning
confidence: 99%